Androgenetic Complete Hydatidiform Moles With p57KIP2-Positive Immunostaining. Issue 6 (20th July 2020) - Usui, Hirokazu; Sato, Asuka; Ota, Masayuki; Ikeda, Jun-ichiro; Shozu, Makio
Abstract: Objectives: Complete hydatidiform moles (CHMs) are androgenetic and have a high rate of progression to gestational trophoblastic neoplasia (GTN). CHMs are negative when immunostained for p57KIP2 protein, the product of the maternally expressed gene on chromosome 11p15.5, whereas biparental partial hydatidiform moles and hydropic abortion are positive for p57KIP2. This study presents two cases of p57KIP2-positive androgenetic CHMs and explores the cause of this inconsistency. Methods: Androgenetic CHMs were diagnosed using multiplex short tandem repeat polymorphism analysis. Single-nucleotide polymorphism arrays were performed for molecular karyotyping. Results: Among the consecutive 188 androgenetic CHMs, two cases were positive for p57KIP2. The first case remitted spontaneously, whereas the second case developed into low-risk GTN. The first case was positive for p57KIP2 in all villi. The karyotype was 48, XX, +7, +11, with the additional chromosome 11 confirmed to be of maternal origin. The second case presented a mosaic of both positively and negatively stained villi. The karyotype was 46, XX. Conclusions: The cause of one of the CHMs was trisomy with an additional maternal chromosome 11. Although rare, the confirmation of p57KIP2-positive androgenetic CHM status is necessary to manage GTN risk.